1988
DOI: 10.3354/meps044025
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory electron transport system (ETS) activities in zooplankton and micronekton of the Indo-Pacific region

Abstract: ETS activities of natural zooplankton assemblages and some micronekton species from the eastern Banda Sea and western Arafura Sea (Indonesia) were measured during the SE and NW monsoons, when respectively rich upwehng and poor downwelling condtlons occur. Weight-specific ETS activities of the zooplankton community decreased with depth; 13 to 20 % of this decrease was related to temperature, and another 5 to 10 % to hlgher water contents of the deeper samples. Large geographical dfferences, but no seasonal diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
(51 reference statements)
6
11
0
1
Order By: Relevance
“…ETS activity is assumed to represent the maximum potential oxygen consumption rate (see Pfeiler and Govoni 1993). This study clearly showed a decrease in wet-weight-specific ETS activity with increase in body length in premetamorphic leptocephali (Pfeiler and Govoni 1993), which was consistent with a previous ETS activity study that included leptocephali (Schalk 1988). Bonefish leptocephali were also tested in respirometers, which showed that respiration rates increased during metamorphosis as GAG and other materials were converted into respiring tissues (Pfeiler and Govoni 1993).…”
Section: -5 Physiology and Energeticssupporting
confidence: 87%
“…ETS activity is assumed to represent the maximum potential oxygen consumption rate (see Pfeiler and Govoni 1993). This study clearly showed a decrease in wet-weight-specific ETS activity with increase in body length in premetamorphic leptocephali (Pfeiler and Govoni 1993), which was consistent with a previous ETS activity study that included leptocephali (Schalk 1988). Bonefish leptocephali were also tested in respirometers, which showed that respiration rates increased during metamorphosis as GAG and other materials were converted into respiring tissues (Pfeiler and Govoni 1993).…”
Section: -5 Physiology and Energeticssupporting
confidence: 87%
“…The vertical distribution pattern of euphausiids does not seem to be at all correlated to the carbon consumption ver tical trend during the 24 h cycle. As previously reported (Torres et al 1979, Schalk 1988, Minutoli & Guglielmo 2009, at midday, afternoon and midnight, the vertical distribution of ETS activity in the present study resembled that of euphausiid abundance. On the other hand, in the morning, the high values of ETS activity were not associated with high eu phau siid abundance.…”
Section: Discussionsupporting
confidence: 73%
“…The rate-limiting step of ETS is the coenzyme Q-cytochrome b complex oxidation, that can be measured after the reaction of the complex with the artificial electron acceptor 2-(p-iodophenyl)-3-(p-nitrophenyl)-5-phenyl tetrazolium chloride (INT) (Pa ckard 1971). This reaction is influenced by various factors, such as temperature, salinity and sexual stage (Torres et al 1979, Ikeda & Fay 1981, Raymont 1983, Schalk 1988, even if adaptations to environmental conditions are possible (Anraku 1964, Musayeva & Shushkina 1978, Båmstedt 1980, Hirche 1984. Several papers have shown a good correlation between ETS activity and in vivo respiration (Packard et al 1974, Kenner & Ahmed 1975, Owens & King 1975, Devol & Packard 1978, so that ETS activity can be used as an estimate of mesozooplankton respiration rates.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of storage of the homogenate prior to the ETS assay was reviewed recently by Schalk (1988) and the literature is contradictory. Part of the explanation may be that some of the observations in previous studies were so infrequent that an initial increase might have been overlooked if it were followed in turn by a rapid decrease.…”
Section: Discussionmentioning
confidence: 99%